Alcohol and cigarette use and misuse among hurricane Katrina survivors: Psychosocial risk and protective factors - Flory, Kate (2014)
The present study examined survivors’ use and misuse of cigarettes and alcohol following Hurricane Katrina. We also examined several psychosocial factors that we expected would be associated with higher or lower rates of substance use following the Hurricane. Participants were 209 adult survivors of Hurricane Katrina interviewed in Columbia, SC or New Orleans, LA between October 31, 2005 and May 13, 2006. Results revealed that survivors were smoking cigarettes, consuming alcohol, and experiencing alcohol-related problems at a substantially higher rate than expected based on pre- Hurricane prevalence data. Results also suggested that certain psychosocial factors were associated with participants’ substance use and misuse following the Hurricane.